A compendious investigation of Android malware family. (2016) - Dayal, Mohit; Nagpal, Bharti
Number of malicious programs for Android is rising at explosive rate. McAfee security vendor has mentioned in report, that Android platform is the most vulnerable target for hackers and by now, around six millions unique malware programs have been observed. The most rampant Android malicious program is found to be SMS Trojans, discerned by experts. Man-in-middle (MiM), man-in-the-mobile (MitMo), etc. are examples of SMS Trojans. The second common troop of threat belongs to plangton, hamob, AdWare, AndroidOS. These are detected as Trojans, but are useful type of apps. All these apps what does is, demonstrate advertising. The last group of malware is more dangerous as it made hackers to get root access on Android operating system of various smart-phones. So, to increase secure usage, preventive measures against such attacks are necessary. In this paper, we author have discussed Android malware family, its types, lifecycle, attacking mechanism, patch cycle and concluded with the comparative analysis of various existing Android malware.